PENGARUH MEDIA POHON PINTAR TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN ANAK USIA 4-5 TAHUN DI TK MUTHIAH ISLAMIC SCHOOL KAYUAGUNG - Nurjanah; Akmillah Ilhami (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low level of number concept knowledge among children aged 4-5 years. The purpose of this study was to determine the effect of the smart tree media on number concept understanding in children aged 4-5 years.This study used a quantitative approach with a quasi-experimental (pre-experimental) method through a single-group pretest-posttest design. The sample consisted of 16 children in Group A at Muthih Kindergarten, Kayuagung, selected using a saturated sampling technique. Data were collected through structured observations using checklists and worksheets (LKPD) compiled based on indicators of number concept understanding. Data analysis included validity and reliability tests, a chi-square normality test, and a t-test hypothesis test. The results of the normality test indicated a normal distribution (x² calculated ≤ x² table). The hypothesis decision-making process was based on a t-test analysis; if t² calculated ≥ t², then Ho is rejected and Ha is accepted. So it is concluded that t count ≥ t table (4.38 ≥ 1.75) so it can be said that Ho count is rejected and Ha is accepted. Thus, the use of smart trees can be concluded that there is a significant influence of Smart Tree Media on the ability to recognize number concepts in children aged 4-5 years at TK Muthiah Islamic School Kayuagung.